Expectational Bottlenecks and the Emerging of New Organizational Forms - Giorgio Rampa; Francesco Bogliacino (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
In this article we discuss the dynamics of organizational change when agents have heterogeneous initial conjectures and do learn. In this framework, conjectural equilibrium is defined as a steady state of the learning process, and all the adjustment occurs in disequilibrium. We discuss the properties of the system under different rationality assumptions, and using well-known learning algorithms. We prove analytically that multiplicity of equilibria, and failure of good organizational routines, cannot be ruled out: better, they are fairly probable. Stability is a crucial matter: it is shown to depend on initial conjectures. Finally, learning does not necessarily select the best.
Keywords: C67; E01; F14; 330